2008
DOI: 10.1007/s10528-008-9164-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Among Turkish Native Chickens, Denizli and Gerze, Estimated by Microsatellite Markers

Abstract: The genetic diversity of the Turkish native chicken breeds Denizli and Gerze was evaluated with 10 microsatellite markers. We genotyped a total of 125 individuals from five subpopulations. Among loci, the mean number of alleles was 7.5, expected heterozygosity (H e ) was 0.665, PIC value was 0.610, and Wright's fixation index was 0.301. H e was higher in the Denizli breed (0.656) than in the Gerze breed (0.475). The PIC values were 0.599 and 0.426 for Denizli and Gerze, respectively. A phylogenetic tree was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
5
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 16 publications
5
47
5
5
Order By: Relevance
“…To breed chickens or commercial lineages (broiler or laying hens), the average number of alleles per locus ranged of 1.3 to 8.1 in studies of Croojimans et al (1996) To non-commercial birds, the values of medium alleles per locus observed were from 3.4 to 9.3 (Hillel et al 2003, Kaya et al 2008, Nasiri et al 2007, Nassiri et al 2007, Shahbazi et al 2007, Zhang et al 2002. These higher values in non-commercial chickens in relation to the commercials are due to a strong pressure of artificial selection that the latter suffer.…”
Section: Resultsmentioning
confidence: 99%
“…To breed chickens or commercial lineages (broiler or laying hens), the average number of alleles per locus ranged of 1.3 to 8.1 in studies of Croojimans et al (1996) To non-commercial birds, the values of medium alleles per locus observed were from 3.4 to 9.3 (Hillel et al 2003, Kaya et al 2008, Nasiri et al 2007, Nassiri et al 2007, Shahbazi et al 2007, Zhang et al 2002. These higher values in non-commercial chickens in relation to the commercials are due to a strong pressure of artificial selection that the latter suffer.…”
Section: Resultsmentioning
confidence: 99%
“…(Bilgen et al, 1999;Aksoy et al, 2000). Since the 2000s, in order to determine genetic variation, some molecular studies based on DNA have been conducted in Turkey (Ivgin and Bilgen, 2002;Okumus and Kaya, 2005;Kirdag, 2007;Kaya and Yildiz, 2008;Taskesen, 2010;Mercan and Okumus, 2015). Initially, genetic distance and similarities were detected among meat and layer pure line chickens in Turkey, using the RAPD technique (Ivgin and Bilgen, 2002;Okumus and Kaya, 2005); MtDNA variations were also detected in native and commercial populations.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial DNA D-loop and 12S regions were studied in Denizli native chicken and the result of the study gave informative data for local breed in Turkey (Karaman and Kirdag, 2012). The microsatellite genetic variations of two native breeds, Denizli and Gerze, were determined to be ten microsatellites (Kaya and Yildiz, 2008). The genetic structures of local chicken populations of the Central Black Sea region and two commercial chicken populations in Turkey, were determined and compared using twenty eight microsatellite loci (Mercan and Okumus 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are numerous and commonly marker used in nuclear DNA analyzes. The microsatellites have a codominant inheritance, being easily to identify and polymorphic (KAYA & YILDIZ, 2008). This study aimed to evaluate with microsatellites markers the genetic variability of these two free range chicken lines (broiler and layer) and compare the results with others chickens (commercial or no-commercial).…”
Section: Introductionmentioning
confidence: 99%